(untitled) (Global Journal of Medical Research, 2014)
In india there are many barriers to initiation of breast feeding within one hour of birth. This study was done with the aim of evaluating whether verbal counseling of pregnant women during the antenatal period can help improve the incidence of early initiation of breast feeding. A prospective, questionnaire based study including 100 pregnant females, was conducted a tertiary care hospital of Delhi. The patients were randomly allotted to two groups. Group A received verbal antenatal counseling regarding benefits of early intiation and group B did not. The proportion of women initiating breast feeding within one hour of birth was then assessed and both groups were compared. Results: In group A (conselled group) 58 % women intiated breast feeding within one hour of birth while in the control group (without conselling) 32 % women did early intiation. The difference was statistically significant. (p= 0.0090 Verbal counseling is a simple inexpensive intervention that can be easily done during antenatal visits to motivate pregnant women for early intitation of breast feeding but is sadly often overlooked. This study shows that simple measures like verbal counseling can improve the early initiation of breast feeding.